E-learning program for medical students in dermatology (Clinics, 2011)
INTRODUCTION: Dermatological disorders are common in medical practice. In medical school, however, the time devoted to teaching dermatology is usually very limited. Therefore, online educational systems have increasingly been used in medical education settings to enhance exposure to dermatology. OBJECTIVE: The present study was designed to develop a e-learning program for medical students in dermatology and evaluate the impact of this program on learning. METHODS: This prospective study included second year medical students at the University of Technology and Science, Salvador, Brazil. All students attended discussion seminars and practical activities, and half of the students had adjunct online seminars (blended learning). Tests were given to all students before and after the courses, and test scores were evaluated. RESULTS: Students who participated in online discussions associated with face-to-face activities (blended learning) had significantly higher posttest scores (9.0 + 0.8) than those who only participated in classes (7.75+1.8, p